Just use the Remainder Theorem.
The Remainder Theorem states that
"The assertion that P(c) is the remainder when polynomial P(x) is divided by x – c."
That is, remainder = P(c) , the value of P(x) at x = c.
In your problem, P(x) = x^3 + 3x^2 - 2x + 7 and c = -1.
So, Remainder = P(-1)
= (-1)^3 + 3(-1)^2 -2(-1) + 7
= (-1) + 3 + 2 + 7
= 11
Thus, when x^3 + 3x^2 -2x + 7 is divided by (x+1), the remainder is equal to 7.
2006-09-26 16:11:16
·
answer #1
·
answered by Hanz 2
·
0⤊
0⤋
you can solve the problem using long divison just like regular numbers.
x+1 | x^3+3X^2-2x+7
you start on the left to see what you can divide x+1 into. You start off with x^3. You can make x^3 if you multiply x+1 by x^2. That gives you (x+1)*x^2 = x^3 + x^2. You subtract that from the larger expression, and get rid of the x^3. You are left with: 2x^2 - 2x + 7.
Repeat. What do you multiply x+1 with so that you can get rid of 2x^2? (x+1) * 2x = 2x^2 + 2x. Subtract that from 2x^2-2x+7 and you get: -4x+7.
Repeat again. This time you have (x+1) * -4 = -4x-4. Subtract that from -4x+7 and you have 11.
Thus, x^3 + 3x^2 - 2x + 7 divided by x + 1 is x^2 + 2x - 4 + 11/(x+1)
2006-09-26 16:04:25
·
answer #2
·
answered by Matichel 4
·
1⤊
1⤋
x+1=-1 (substitute the -1 to x3+3x2-2x+7)
remainder=(-1)^3+3(-1)^2-2(-1)+7
r=-1+3+2+7
r=12-1
r=11
2006-09-27 02:41:17
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
(x^2)+2x-4+(11/x+1) this is the restult. Your remainder is 11.
2006-09-26 16:02:42
·
answer #4
·
answered by Herman 4
·
0⤊
0⤋
11
(x^3+3x^2-2x+7)/(x + 1) = (x^2+2x-4) +11/(x+1)
2006-09-26 15:57:06
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
(x^3 + 3x^2 - 2x + 7)/(x + 1)
-1`|`1``3`-2`|`7
```|````-1``-2`|`4
-----------------------
```|`1```2``-4`|`11
x^2 + 2x - 4 R 11
ANS : 11
2006-09-26 16:29:10
·
answer #6
·
answered by Sherman81 6
·
0⤊
0⤋
remainder is 11
2006-09-26 15:58:19
·
answer #7
·
answered by sgrockergirl 2
·
0⤊
0⤋
I dont have to solve it for you just remember this word all the time when solving problems like these "BODMAS"
B is Bracket
O Is off
D Is divide
M is Multi ply
A Is Add
S is Subtract
The reason I did not solve the question is not clear.
2006-09-26 16:01:47
·
answer #8
·
answered by Dr.O 5
·
0⤊
0⤋